Effects of tDCS on Depression and Comorbid Generalized Anxiety Disorder: A Brain Function Imaging Case Report - Wu, Yuwei; Tang, Lin; Shi, Xiaolong; Zhou, Zhiqing; Li, Yuanli; Shan, Chunlei (Frontiers in Neurology, 2022)
Background Transcranial direct current stimulation (tDCS) is a type of non-invasive brain stimulation technique that has proven effective for neuropsychiatric disorders. Generalized anxiety disorder (GAD) and depression are common psychiatric disorders that often are comorbid, meaning they occur simultaneously. Current evidence supports the value of tDCS for GAD. The objectives of this report is to explore the effect of tDCS on clinical symptoms and cerebral function in a patient with comorbid GAD and depression. Methods Our subject was a semiprofessional athlete diagnosed with comorbid GAD and depression. Symptoms included palpitations, sweating, continuous tension, and anxiety. We designed a B-A-B experimental protocol and used the Beck Anxiety Index (BAI), Beck Depression Index (BDI), and Pittsburgh Sleep Quality Index (PSQI) as assessment tools. Treatment consisted of 2 series of 15 days each, separated by a 3-week washout period. We collected functional near-infrared spectroscopy (fNIRS) data before and after both series, as well as fNIRS data immediately after the first treatment in both series. In addition, we collected functional magnetic resonance imaging data before and after the second series. Results After the first series, the scores of the three questionnaires (BAI, BDI and PSQI) decreased significantly, which showed the trend of improvement. The functional connection of bilateral prefrontal partial channels decreased significantly immediately after tDCS treatment. The results of the fNIRS before the second-series treatment showed that prefrontal connectivity returned to the state before the first intervention after the washout period. The results of the fNIRS after the second series treatment showed that the symptoms of depression and anxiety alleviated. The results of the fNIRS showed that the prefrontal connectivity decreased again. Conclusion In the treatment of comorbid GAD and depression, tDCS can alleviate symptoms and improve sleep quality and social behavior. Brain imaging is widely used to observe functional changes by tDCS such as fMRI and fNIRS. The study also showed that fNIRS can be a safe, simple, and efficient method to assess brain activity.